An Elusive Passage of the Earlier Funerary Literature in its Iconographic and Ritual Context - Goebs, Katja (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
Pyr . 398c–399a, which describes the deceased king as seated “with his back to Geb”, is re-examined in relation to its co- and context within the Cannibal Spell, as well as being set against some hitherto overlooked iconographic and textual evidence from other sources. A new interpretation of the passage as relating to the rituals of royal legitimization is proposed.